HUBUNGAN ANTARA KESIAPAN MENTAL DENGAN MOTIVASI BELAJAR PADA MATA PELAJARAN BIOLOGI - Tri Sutasmi Nirwan; Muh Rapi; Muchlisah Muchlisah (Jurnal Biotek, 2016)
This study discusses the relationship of mental readiness with motivation to learn for Biology lesson of Learners at SMA Negeri 1 West Bajeng Gowa. This Research aims to review the readiness view of mind of the  Learners which follow the subjects of Biology in SMA Negeri 1 West Bajeng Gowa, and to know the Relationship  between mental readiness and motivation to learn on the subjects of Biology for the students of SMA Negeri 1 West Bajeng Gowa.           This type of research is correlational . This research was held in SMA Negeri 1 West Bajeng, Gowa. The research sample is 156 people students. The analysis technique used is the analysis of descriptive statistics and inferential statistical analysis.Results of descriptive statistics , mental readiness obtained average value of 79.69 in middle category, with percentage of 69.78 % . For motivation to learn obtained average value of 101,07 in middle category,with a percentage of 69.23 % . Thus , it can be concluded that the F count > F table ie 8.612 > 3.90 , then H0 rejected and Ha accepted, meaning that the hypothesis is accepted .There is a relationship between mental readiness and motivation to learn in the subjects of Biology on the students of SMA Negeri 1 West Bajeng Gowa with the correlation value ( R) of 0.418 ( included in the category of moderate correlation)